(untitled) (Nepalese Veterinary Journal, 2023)
We carried out this study to assess the quality of semen regarding the seasonal and geographical variability of Murrah buffalo breeding bull in Nepal. We aimed to access the quality of seme n of murrah buffalo bull considering the seasonal and geographical variability to help standardize quality semen producing protocol and concern. A total of eight Murrah buffalo bulls were used. Semen collection was done at once week and two ejaculations were considered at an interval of 30 minutes during the Summer (June to August), Autumn (September to November), Winter (December to February), and Spring (March to May) from 2017 to 2020 AD. Immediately after collection, initial motility, sperm concentration, pre-filling motility, post-thaw motility, live sperm, and abnormality of sperms were evaluated. Findings revealed that the season had affect (p<0.005) to the semen volume, individual motility, and post- thawing motility except for semen volume and sperm abnormality(p>0.05). However, initial motility, sperm concentration, and pre filling motility did not vary in months (p>0.05). It is thus well reflected that several traits related to quality and quantity of semen Murrah buffalo bulls may vary depending on the season of collection, location and age (p<0.05) with the semen traits of initial motility, sperm concentration, and pre-filling motility. Accordingly the semen collected during the autumn and spring season is revealed the percentage of average post thaw motility above the 52% that considered the success of artificial insemination is good for buffaloes.